Co-existing inflammatory bowel disease and Barrett’s esophagus is associated with esophageal dysplasia: a propensity score-matched cohort - Fasullo, Matthew; Sreenivasen, Aditya; Holzwanger, Erik; Lavender, Charles; Patel, Milan; Shah, Tilak; Mutha, Pritesh; Yacavone, Robert F.; Sultan, Keith; Trindade, Arvind J.; Smallfield, George (Endoscopy International Open, 2021)
Background and study aims Barrettʼs esophagus (BE) and inflammatory bowel disease (IBD) predispose to the development of dysplasia and cancer. It is unclear if the inflammatory cascade seen in IBD affects disease progression in BE. We aimed to determine if patients with BE who have co-existing IBD had a higher risk of dysplasia, nodular disease, or longer segments than BE patients without IBD.Patients and methods This was a multicenter, retrospective propensity score-matched cohort study. We compared rates of dysplasia, nodular disease, and segment length in patients with BE and IBD (cases) to patients with BE who did not have IBD (controls). Controls were 1:1 propensity score matched with controls for age, sex, body mass index (BMI), smoking, and hiatal hernia.Results A total of 132 patients were included in the IBD + BE group and 132 patients in the BE group. Patients with IBD + BE had higher rates of esophageal dysplasia compared to controls (15.9 % vs. 6.1 % [adjusted odds ratio [OR]: 2.9, 95 % CI: 1.2–6.9]) and more nodules (9.8 % vs. 3.0 % [adjusted OR: 3.5, 95 % CI: 1.1–11.0]). IBD + BE group was also associated with longer BE segments (43.9 % vs. 12.1 % [OR: 5.7, 95 % CI: 3.0–10.6]).Conclusions Co-existing IBD may increase the risk of dysplasia and esophageal nodules in patients with BE. Our findings may have implications for BE surveillance intervals in IBD patients. Prospective studies are needed to confirm our findings.